Determination of vanadium (IV) and vanadium (V) using voltammetric and ion chromatographic techniques [electronic resource] - Tengku Sharifah Marliza Tengku Azmi, 1982-; Fakulti Sains (2009)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2009